An oleuropein rich-olive (Olea europaea L.) leaf extract reduces β-amyloid and tau proteotoxicity through regulation of oxidative- and heat shock-stress responses in Caenorhabditis elegans. (April 2022) - Romero-Márquez, Jose M.; Navarro-Hortal, María D.; Jiménez-Trigo, Victoria; Vera-Ramírez, Laura; Forbes-Hernández, Tamara J.; Esteban-Muñoz, Adelaida; Giampieri, Francesca; Bullón, Pedro; Battino, Maurizio; Sánchez-González, Cristina; Quiles, José L.
Abstract: Olive tree-derived products have been associated with numerous benefits for health. The aim of the present study was to characterize an olive leaf extract enriched in oleuropein (OLE) concerning phenolic content and profile as well as antioxidant capacity. Short-term and long-term toxicity, including oxidative stress, was in vivo evaluated in the experimental model Caenorhabditis elegans . Moreover, the potential therapeutic effect of the extract against Aβ induced- and tau protein induced-toxicity was also evaluated in C. elegans . OLE treatment did not exert toxicity. On the contrary, the extract was able to ameliorate oxidative stress and proteotoxicity related to Aβ and tau aggregation. The potential molecular mechanisms present behind the observed results explored by RNAi technology revealed that DAF-16/FOXO and SKN-1/NRF2, elements of the insulin insulin-like signalling pathway, as well as HSP-16.2 overexpression were involved. Graphical abstract: Image 1 Highlights: ● OLE is a source of phenolics that exert a strong antioxidant effect in vitro. ● Short- and long-term toxicity, including oxidative stress, is prevented by OLE. ● OLE prevented Aβ peptide and tau protein induced toxicity in C. elegans. ● DAF-16/FOXO, SKN-1/NRF2 and HSP16.2 are involved in OLE anti-AD effects. ● OLE could be an interesting formulation for the development of nutraceutics.